2020
DOI: 10.1016/j.cmi.2019.09.009
|View full text |Cite|
|
Sign up to set email alerts
|

Machine learning for clinical decision support in infectious diseases: a narrative review of current applications

Abstract: Background: Machine learning (ML) is a growing field in medicine. This narrative review describes the current body of literature on ML for clinical decision support in infectious diseases (ID). Objectives: We aim to inform clinicians about the use of ML for diagnosis, classification, outcome prediction and antimicrobial management in ID. Sources: References for this review were identified through searches of MEDLINE/PubMed, EMBASE, Google Scholar, biorXiv, ACM Digital Library, arXiV and IEEE Xplore Digital Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
205
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(210 citation statements)
references
References 94 publications
2
205
0
3
Order By: Relevance
“…The design of our study does not allow to easily separate what is directly related to the M-PCR results from the impact of a multidisciplinary review of each le. As with other innovative tools, 39 clinical trials, preferably randomized and multicentric, should be conducted to evaluate clinical outcomes, including adverse outcomes, process improvement and ecological impact. Special attention should be paid to the integration and implementation of systems into clinical practice, and their adoption and utilisation by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The design of our study does not allow to easily separate what is directly related to the M-PCR results from the impact of a multidisciplinary review of each le. As with other innovative tools, 39 clinical trials, preferably randomized and multicentric, should be conducted to evaluate clinical outcomes, including adverse outcomes, process improvement and ecological impact. Special attention should be paid to the integration and implementation of systems into clinical practice, and their adoption and utilisation by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…52 Schinkel et al performed a review similar to ours by searching only PubMed, but they excluded studies that did not have an AUROC statistic. 53 No search query is perfect; in fact, Salvador-Olivan et al found that almost 93% of search strategies in systematic reviews contained at least one error in their respective search queries. 54…”
Section: Limitations In Search Strategymentioning
confidence: 99%
“…ML is a branch of artificial intelligence that consists of conferring on computers the ability to learn from data [14,15]. Differently from classical computer expert systems, which are explicitly programmed to do specific task/s (e.g., recognizing a patient to be at risk of MDR-GNB infection), ML algorithms have a notable advantage in term of flexibility, since they may be able to point out the association between patients' characteristics (the input) and the risk of MDR-GNB infection (the output) without being explicitly programmed to do so [16].…”
Section: In Briefmentioning
confidence: 99%